Empirical performance of the Czech and Hungarian index options under jump - Gabriel S. Lee; Michael Boss; Chris Klisz (Institute for Advanced Studies (IHS), 2001)
This paper analyses Czech and Hungarian index options that are traded on the Austrian Futures and Options Exchange. We find that the Poisson jump-diffusion and not the GARCH (1,1) process lends statistical support for the data description. We estimate that approximately four-fifth of 4 percent underpricing (for the Czech Index) and 18 percent overpricing (for the Hungarian Index) biases reported for the short term out-of-the-money call options can be explained by the Jump option pricing model. However, we question whether the mispricings from the jump model are operational, especially, in these emerging financial markets.
Keywords: C52; G13; C51; C52; 330; Leptokurtosis; poisson jump-diffusion; GARCH; equity index options; Index-Futures; Tschechisch; Ungarisch; Volatilität; Zeitreihenanalyse; Österreich